2021
DOI: 10.1126/sciadv.abe6563
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota control of maternal behavior regulates early postnatal growth of offspring

Abstract: Maternal behavior is necessary for optimal development and growth of offspring. The intestinal microbiota has emerged as a critical regulator of growth and development in the early postnatal period life. Here, we describe the identification of an intestinal Escherichia coli strain that is pathogenic to the maternal-offspring system during the early postnatal stage of life and results in growth stunting of the offspring. However, rather than having a direct pathogenic effect on the infant, we found that this pa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 61 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…It is well accepted that neurodevelopment is susceptible to changes in early life, and the impacts of maternal care on neurodevelopment have been highly investigated 53 55 . More recently, it has been shown that the fetal and infant microbiome is also dynamic and shares similar susceptibilities to early life changes dependent on infant-mother interactions 5 , 56 58 . Maternal diet can also influence offspring microbiome diversity, as the ratio of Firmicutes to Bacteroidetes in HFD-fed mothers is shared by their non-HFD-fed offspring 59 , 60 .…”
Section: Introductionmentioning
confidence: 99%
“…It is well accepted that neurodevelopment is susceptible to changes in early life, and the impacts of maternal care on neurodevelopment have been highly investigated 53 55 . More recently, it has been shown that the fetal and infant microbiome is also dynamic and shares similar susceptibilities to early life changes dependent on infant-mother interactions 5 , 56 58 . Maternal diet can also influence offspring microbiome diversity, as the ratio of Firmicutes to Bacteroidetes in HFD-fed mothers is shared by their non-HFD-fed offspring 59 , 60 .…”
Section: Introductionmentioning
confidence: 99%
“…Changes in community structure could result in functional changes, and then affect host health. For instance, adiposity and insulin insensitivity were increased in germ-free mice receiving the intestinal microbiota from women in late pregnancy compared to those in mice inoculated with the gut microbiota of women in early pregnancy ( Koren et al, 2012 ), thus affecting innate immune function and fetal development and health ( Gomez de Agüero et al, 2016 ; Lee et al, 2021 ) by regulating the incipient microbial biomass and communities of offspring ( Perez-Muñoz et al, 2017 ; Bi et al, 2021 ). Furthermore, gut microbiota changes may directly influence maternal metabolic alterations related to pregnancy ( Koren et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…The early postnatal period of life is a vital stage for growth and development. The intestinal microbiota has emerged as a critical regulator of growth and development in the early postnatal period of life ( Lee et al, 2021 ). The intestinal microbiota is deemed to coincide with the development of our body systems ( Cowan et al, 2020 ; Wilkins and Reimer, 2021 ).…”
Section: Introductionmentioning
confidence: 99%